ANALISIS FAKTOR – FAKTOR YANG MEMENGARUHI KEPUTUSAN PEMBELIAN DI MARACA BOOKS AND COFFEE - Haifa Fatinah Mutiksa; Ma'mun Sarma (Jurnal Manajemen Pembangunan Daerah, 2025)
ABSTRACT Increased number of coffee shop visitors in Indonesia showed the level of lifestyle is increasing while the level reading interest of Indonesian people is still very low. This phenomenon tend to businessmen to develop their innovation. They make a library café, a coffee shop that also facilitate for reading many kind of books. The analytical method used are descriptive analysis and factor analysis. The results of this research show there are eight new factors that affect consumer purchasing decisions, namely interest of books and convenience of reading, quality of coffee product, quality of service, personal attractiveness, interest of coffee, eco-friendly, supporting facilities and influence of friendship. Keywords: factor analysis, Maraca Books and Coffee, purchasing decision